Impacts of Oreochromis mossambicus (Perciformes: Cichlidae) upon habitat segregation among cyprinodontids (Cyprinodontiformes) of a species flock in Mexico - Linda Fuselier (Revista de Biología Tropical, 2001)
Five species of Cyprinodon in Laguna Chichancanab, Yucatan, Mexico comprise a young species flock whose ecology and evolution has not been thoroughly studied, but whose existence is threatened with extinction. Species flocks evolve in isolated areas where predators and competitors are absent. Since the description of the Chichancanab flock, Oreochromis mossambicus, a species introduced into the lake for which I examined habitat in the 1980’s, has become common throughout the basin. I assessed relative abundance of flock species in the lake. examined habitat use and segregation among the three most common flock species and examined the affects of O. mossambicus upon flock species habitat use. Cyprinodon beltrani was the most abundant flock species in 1997, followed by C. maya and C. labiosus; C. verecundus and C. simus were rare. Cyprinodon beltrani was found in shallow water, nearshore, over thick beds of submerged Chara, and little emergent vegetation Cyprinodon beltrani exhibited diurnal variation in nearshore habitat use. In the field, the habitat use of C. beltrani and O. mossambicus broadly overlapped. In aquarium experiments, three flock species exhibited habitat use segregation and C. beltrani and C. labiosus showed agonistic behaviors that strengthened segregation. Cyprinodon maya differed from C. beltrani and C. labiosus by its greater dispersion of individuals and use of areas higher in the water column. The presence of O. mossambicus caused a shift in habitat use by C. maya and C. labiosus that put these species into habitat occupied by C. beltrani. The presence of introduced species has caused a significant perturbation of the conditions that fomented speciation of the Chichancanab flock 8000 years ago. Cinco especies de Cyprinodon en la Laguna Chichancanab, Yucatán, México comprenden un cardumen jóven de especies cuya ecología y evolución no ha sido estudiada a fondo, pero cuya existencia está siendo amenazada con la extinción. Los cardúmenes de peces evolucionan en áreas aisladas donde los depredadores y los competidores están ausentes. Desde la descripción del cardumen de Chichancanab, Oreachromis mossambicus, una especie introducida al lago de la cual yo examiné el hábitat en los 80's, se ha vuelto común en toda la laguna. Yo evalué la abundancia relativa de especies del cardumen en el lago y uso de hábitat y segregación entre la especies del cardumen más comunes y examiné los efectos de O. mossambicus en el uso de hábitat de las especies del cardumen. Cyprinodon beltrani fué la especie de cardumen más abundante en 1997, seguida por C. maya y C. labiosus; C. verecundus y C. simus fueron muy raras. Cyprinodon beltrani fue encontrada en aguas someras, cerca de la costa, sobre lechos densos de Chara y poca vegetación emergente. Cyprinodon beltrani exhibió variación diurna en el uso del hábitat cerca de la costa. En el campo, el uso de hábitat de C. beltrani y O. mossambicus se traslapaban ampliamente. En experimentos en acuarios, tres especies de cardumen exhibieron segregación de uso de hábitat y C. beltrani y C. labiosus mostraron comportamientos agonísticos que fortalecen la segregación. Cyprinodon maya se diferencia de C. beltrani y C. labiosus por su mayor dipersión de individuos y uso de áreas más altas en la columna de agua. La presentación de O. mossambicus causó un cambio en el uso de hábitat de C. maya y C. labiosus que puso a estas especies dentro del hábitat ocupado por C. beltrani. La presencia de esta especie introducida ha ausado una perturbación significante de las condiciones que fomentaron especiación de cardumen de Chichancanab hace 8 000 años.